Simulation et commande d’un Drone Quadrirotor en utilisant la logique floue - DEHINA Khadidja lina; NOUIOUA Mohammed nassim; M. BENMOUIZA Khalil (Université Amar Thelidji- Laghouat.FACULTE : TECHNOLOGIE.DEPARTEMENT : ELECTROTECHNIQUE, 2022)
An unmanned aerial vehicle or drone is essentially a flying robot that can be remotely controlled or fly autonomously via software-controlled flight plans in their integrated systems, working in conjunction with on-board sensors and GPS. Modeling, identification and control of quadcopter drones is known as a difficult task due to the non- linearity presented in their dynamic model. In this dissertation, the study of the literature in this field of application is presented. The model of the rigid quadcopter is considered in the modeling. The Euler- Lagrange formalism is used to obtain the dynamic model of the complete system. A simulation in Matlab/Simulink was developed based on the identification of a real quadcopter. The control of the quadrotor is done by conventional PID and Fuzzy PID controllers. The Simulation results validate this strategy and facilitate the control scheme.
OPTION : Automatique et informatique industrielle